Single-slab 3D double inversion recovery for magnetic resonance brain imaging in clinically healthy dogs - Je, Miseong; Yang, Sunho; Lee, Dongjae; Choi, Jihye; Yoon, Junghee (Frontiers in Veterinary Science, 2023)
In veterinary medicine, magnetic resonance imaging (MRI) is widely utilized for brain imaging. But the complex structures of brain tissues can give rise to artifacts such as partial volume averaging in conventional sequences. To address this issue , several studies about double inversion recovery (DIR) sequences have been conducted in human medicine. However, published clinical studies about brain MRI using DIR sequences in dogs are currently lacking. The purpose of this study was to evaluate the magnetic resonance features of single-slab 3D DIR sequences in the normal canine brain. Five healthy Beagle dogs were examined and the following pulse sequences were acquired for each: (1) Spin-echo T2-weighted (T2W), (2) fluid attenuated inversion recovery (FLAIR), (3) gray matter (GM) selective, and (4) white matter (WM) selective single-slab 3D DIR sequence. For qualitative analysis, the distinction between gray and white matter of the cerebral cortex, presence and severity of the image artifacts were assessed for each pulse sequence. In addition, reconstructed images of single-slab 3D DIR sequences were qualitatively evaluated. For quantitative analysis, contrast ratios (CRs), signal-to-noise ratios (SNRs), and contrast-to-noise ratios (CNRs) of the GM, WM and cerebrospinal fluid (CSF) were measured for each pulse sequence. GM selective 3D DIR was superior to T2W and FLAIR in delineating the boundaries between GM and WM in the overall brain area. Whereas WM selective 3D DIR provided better gray-white matter distinction of the cerebral cortex than T2W and FLAIR at the level of the medulla oblongata, where T2W and FLAIR images exhibited severe partial volume averaging artifacts. In general, the 3D DIR images demonstrated fewer artifacts compared to other sequences, and the reconstructed sagittal and dorsal images of these sequences maintained same spatial resolution as the original transverse images without any image degradation. Both gray and white matter selective 3D DIR sequences effectively suppressed unwanted signals, thereby providing high contrast between gray and white matter. Findings from this study could serve as a foundation for further studies on DIR sequences for the evaluation of brain diseases in dogs.